Crisis-proofing real estate: ESG and downside risk resilience in European market shocks. Measuring impact for "BPI Impacto Clima" funds - Provoost, Mathieu Arnaud Laurent (2025)
This thesis examines whether stronger ESG performance strengthened downside resilience in European listed real‐estate firms during two severe shocks, namely the Q1 2020’s COVID‐19 sell‐off and Q3 2022’s energy crisis. Leveraging Refinitiv ESG scores, daily price and volume data, and quarterly financials for 16 firms across varied regulatory stringency, we calculate maximum drawdown, realized volatility, and Sharpe ratios. Cross‐sectional and fixed‐effects regressions reveal no significant ESG impact on drawdown or volatility and a marginal negative crisis‐period Sharpe effect. These findings imply that ESG alone does not ensure crisis resilience, highlighting the need to integrate sustainability metrics with traditional risk‐ management tools.